The Role of Dynamic Contrast-Enhanced MRI in a Child with Sport-Induced Avascular Necrosis of the Scaphoid: A Case Report and Literature Review - Baris Beytullah Koc; Martijn Schotanus; Bob Jong; Pieter Tilman (Case Reports in Orthopedics)
Avascular necrosis (AVN) of the scaphoid in children is very rare and there is currently no consensus when conservative or operative treatment is indicated. A 10-year-old boy, practicing karate, presented with acute pain in his left wrist after falling on the outstretched hand. Imaging showed a scaphoid waist fracture with signs of an ongoing AVN. The diagnosis of AVN was confirmed with signal loss of the scaphoid on MRI T1. A dynamic contrast-enhanced MRI was performed for further assessment of the proximal pole vascularity and treatment planning. As dynamic contrast-enhanced MRI showed fair perfusion of the proximal pole, an adequate healing potential with conservative treatment was estimated. We achieved union and good function with cast immobilization for fourteen weeks. This case study showed dynamic contrast-enhanced MRI to be a valuable tool in assessing whether conservative or operative treatment is indicated to achieve union and good functional outcome.